The Influence of Emotional Intelligence, Job Competence, Education Level, Work Motivation, and Understanding of Good Governance on the Performance of Employees in the Inspectorate Unit of Pohuwato District - Daud, Nurhan; Paramata, Moh. Rolli; Suyanto, Moh. Afan; Karundeng, Deby R. (LPPPIPublishing, 2023)
The purpose of this study was to determine the effect of emotional intelligence, work competence, education level, work motivation and understanding of good governance on the performance of individual employees of the Pohuwato District Inspectorate. The data collection method used in this study was to distribute questionnaires which were measured using a Likert scale. The analytical method used is quantitative analysis with multiple linear regression models. The results showed that (1) emotional intelligence has a significant positive effect on performance. (2) Work competence has no effect on performance (3) Education level has no effect on performance. (4) Work motivation has a positive effect on performance. (5) The understanding of good governance has no effect on the performance of the Pohuwato Regency Inspectorate Work Unit Employees.